Manila interchange the path of transition - Sy, Kennedy M. (College of Architecture, University of the Philippines Diliman, 2018)
The urban core of Metro Manila has been in decay, and not much is being done about it aside from the acceptance that hope lies outside its boundaries, believing that by moving on to better planning of adjacent provinces and cities, change can take place from the outside in. However, right at the center of the City of Manila, an opportunity has been detected for an architectural development that could renew the capital, allowing change to sprawl from the inside out. This development, further explored and detailed in this book, is the Manila Interchange. Located at a dangerous crossroad of the City's two main thoroughfares, the site of the project is where two of Metro Manila's major railways also intersect. Manila interchange utilizes this critical location, its high volume of daily users and the newfound use of urban space, as it attempts to become the Metro's path towards urban renewal.